Perlindungan Hukum Kerugian Franchisee Akibat Perbuatan Melawan Hukum Dalam Perjanjian Waralaba Hanashobu Japanese Noodle Bar - Putri Nur Annisa; Fitika Andraini (UNES Law Review, 2023)
The franchise case fulfills an unlawful act in the case of the Surabaya court decision number 837/Pdt.G/2021/Pn.Sby because the procedure is not in accordance with PP NO.42 of 2007 concerning Franchising and PERMENDAG NO. 31/M-DAG/PER/8/2008 causing losses to franchisees. In the franchise agreement there must be a franchise registration certificate, but in the hanashobu japanese noodle bar franchise agreement there is no STPW. This research is a normative research with descriptive analysis research method. Analysis of the Surabaya court decision number 837/Pdt.G/2021/Pn.Sby. The research results conclude that legal protection is given after a dispute arises or is resolved. In this case the franchisee filed a lawsuit with the Surabaya District Court to get the fairest decision. secondly, after the agreement is declared null and void, the franchisor is responsible for returning the franchisee's losses, both material and immaterial.